Staged arthroscopic procedure for treating simultaneous shoulder and elbow synovial chondromatosis: A case report and literature review - Caiqi Xu; Xingguang Yang (SAGE Open Medical Case Reports, 2020)
It is extremely rare for ipsilateral shoulder and elbow synovial chondromatosis to occur simultaneously. We report a very rare case of simultaneous shoulder and elbow synovial chondromatosis in a 53-year-old woman who was treated through staged surgeries. Shoulder arthroscopic synovectomy, debridement, biceps tenodesis, and subacromial decompression were conducted first, followed by elbow arthroscopy 2 months later. Post surgery, there was no recurrence either clinically or radiologically at 2 years follow-up. Despite some loss of the range of motion of the shoulder and muscle strength, the elbow functions recovered fully, and the patient was extremely satisfied with the clinical outcome. We recommend a staged arthroscopic procedure consisting of a thorough synovectomy and joint debridement for this condition.